Analisis Penyebab dan Dampak Banjir di Perumahan Villa Pamulang, Kecamatan Bojongsari - Satya Valdewa; Cahya Nailah Shafa Syahlani; Mutiara Cinta; Muhammad Athif Raufan Ghifari; Arif Saefudin (Universitas Negeri Gorontalo, 2025)
Flooding is a phenomenon that often occurs in urban areas, including in Villa Pamulang Housing, Bojongsari District, which is influenced by a combination of natural and non-natural factors. This study aims to identify the factors causing floods, analyze the relationship between spatial planning, drainage, and environmental conditions with flood events, describe the social, economic, and public health impacts, and provide recommendations for mitigation strategies. The study uses a qualitative approach with data collection through in-depth interviews with affected residents and direct observation in flood-prone locations, supplemented by visual documentation, and analyzed descriptively to reveal the patterns of causes and impacts of floods. The results indicate that flooding in this area is triggered by the interaction of high rainfall, low topography, soil characteristics, suboptimal drainage, and inadequate spatial planning, thereby increasing the vulnerability of the area to flooding and causing significant social, economic, and health impacts. These findings contribute scientifically to the understanding of the interrelationship between physical conditions of the area, infrastructure, and community behavior with flood risk, and enrich the literature on disaster mitigation and community resilience in urban areas. Practically, this study emphasizes the need to strengthen spatial planning, drainage management, and the development of mitigation programs based on community participation through a community-based disaster management approach, so that communities can not only respond reactively but also take preventive actions to enhance safety, well-being, and community resilience sustainably.